Results of Lisfranc lesions treated with TightRope® fixation – interosseous suture button – minimum follow-up of 5 years - Saito, Guilherme Honda; Cândido Nishikawa, Danilo Ryuko; Fairbanks, Paula Jardim; Sanches de Oliveira Junior, Adilson; Moreira Mendes, Alberto Abussamra; Pires Prado, Marcelo (Journal of the Foot & Ankle, 2026)
Introduction: Open reduction with internal fixation or primary arthrodesis are considered gold standards for the treatment of Lisfranc lesions. However, several disadvantages are associated with these procedures, including loss of joint mobility and potential cartilage damage. More recently, TightRope® has emerged as an alternative treatment for Lisfranc lesions, which can be used alone or in combination with traditional techniques, with the potential to mitigate some of these disadvantages. The primary outcome of the study was to evaluate the functional outcomes of 20 patients treated with the TightRope® technique for Lisfranc lesions. The secondary outcome was to evaluate and describe the complications associated with the procedure. Methods: Retrospective review conducted in 20 patients undergoing surgery for acute Lisfranc lesions using the TightRope® technique. Mean follow-up was 83 months. Clinical evaluation involved assessment of complications, reoperations, midfoot AOFAS scores, VAS scores, patient satisfaction, and ability to return to previous activities. Radiographic analysis was performed to evaluate the maintenance of reduction and the development of osteoarthritis. Results: Patients demonstrated excellent results with a mean AOFAS midfoot score of 95.5 and a mean VAS of 0.50. Incomplete reduction was the only factor that significantly influenced lower AOFAS and VAS scores. Most complications were minimal. Conclusion: The TightRope® technique has been shown to be a reliable alternative for the treatment of acute Lisfranc lesions, providing satisfactory clinical and functional results.